A novel cardiac output response to stress test developed to improve diagnosis and monitoring of heart failure in primary care. (26th June 2018) - Charman, Sarah J.; Okwose, Nduka C.; Stefanetti, Renae J.; Bailey, Kristian; Skinner, Jane; Ristic, Arsen; Seferovic, Petar M.; Scott, Mike; Turley, Stephen; Fuat, Ahmet; Mant, Jonathan; Hobbs, Richard F.D.; et al.
Abstract: Aims: Primary care physicians lack access to an objective cardiac function test. This study for the first time describes a novel cardiac output response to stress (CORS) test developed to improve diagnosis and monitoring of heart failure in primary care and investigates its reproducibility. Methods and results: Prospective observational study recruited 32 consecutive primary care patients (age, 63 ± 9 years; female, n = 18). Cardiac output was measured continuously using the bioreactance method in supine and standing positions and during two 3 min stages of a step‐exercise protocol (10 and 15 steps per minute) using a 15 cm height bench. The CORS test was performed on two occasions, i.e. Test 1 and Test 2. There was no significant difference between repeated measures of cardiac output and stroke volume at supine standing and Stage 1 and Stage 2 step exercises (all P > 0.3). There was a significant positive relationship between Test 1 and Test 2 cardiac outputs ( r = 0.92, P = 0.01 with coefficient of variation of 7.1%). The mean difference in cardiac output (with upper and lower limits of agreement) between Test 1 and Test 2 was 0.1 (−1.9 to 2.1) L/min, combining supine, standing, and step‐exercise data. Conclusions: The CORS, as a novel test for objective evaluation of cardiac function, demonstrates acceptable reproducibility and can potentially be implemented in primary care.